Influences of EU Transport-Specific External Costs on Economic Development - Frantz Daniel FISTUNG; Cornelia NEAGU; Marius BULEARCĂ; Cristian SIMA (Communications of International Proceedings, 2022)
Negative externalities specific to transport are costs imposed on society which, without a policy-administrative intervention, are not taken into account by transporters. Thus, transporters benefit from indirect subsidies, which are economically and morally incorrect, severely unbalancing the relationship between transport demand and supply, which leads to loss of welfare at the level of society as a whole. The calculation methodologies currently used for the monetary assessment of transport-specific external costs are very different and the comparison of the results achieved does not always offer the possibility to adopt common conclusions. It is clear that the transport demand, on an individual level, is affected by the size of revenues and the level of GDP in the country for which the analysis is being carried out. In this context, a causal relationship between individual transport consumption and the GDP of different countries can be established. In the same context, consideration should be given to whether there is a causal relationship between the dimensions of external costs specific to transport and GDP in different countries. The current study presents the analysis of the evolution of indicators relevant to general economic activity and transport in the period 1995-2016 for some countries of the EU. For a more accurate assessment of the contribution of transport activity to GDP formation, the notion of Adjusted Added Value (VAAj) was defined as the real value of the activities carried out in the transport sector, adjusted by the monetary dimension of the negative externalities produced by them. Among the major findings of the current research is the difficulty of identifying a direct link between the level of external costs specific to transport and the general economic development. However, it is suggested that the replacement of Gross Added Value (VAB) by VAAj can quite clearly influence the evolution of GDP value, which may be a way of highlighting the link between economic development and the size of transport-specific external costs.
Keywords: External costs transport; Adjusted added value; Sustainable mobility